PERAWATAN KEHAMILAN DALAM BUDAYA SUKU TETUN - Maria Paula Marla Nahak; Elisabeth Rohan; Angela Muryanti Gatum (NHM PRESS, 2023)
Cultural malpractices during pregnancy are the root cause of maternal and child health problems in rural areas. This study aims to explore the practices of traditional pregnancy care in Tetun tribe. This was a qualitative study with phenomenology approach conducted at Silawan village, Belu Regency, East Nusa Tenggara, Indonesia on January-February, 2019. Informants in this study were 5 pregnant women dan 5 family members, selected by purposive sampling. This study reveals that Pregnant women in Silawan still perform traditional pregnancy care by conducting abdominal massage by traditional birth attendant, using coconut oil and holy water. Pregnant women are suggested to avoid some foods such as egg, octopus, shrimp, fish and rice crust. Traditional pregnancy care still done by pregnant women. Prevention needs to be done by improving health promotion and integrating cultural beliefs and professional health care.